The relationship between the level of periodontal pocket depth with gingival crevicular fluid weight using analytical balance as an indicator of periodontal tissue inflammation - Fauzia Malianawati; Roeswahjuni Neny; Priyanto Rahmavidyanti; Pratiwi Ariyati Retno; Firani Novi Khila; Amelia Monica (Acta Stomatologica Naissi, 2022)
Background: The present study aims to determine the relationship between the level of periodontal pocket depth with the weight of gingival crevicular fluid (GCF)using an analytical balance. Material and Methods: This is an observational analytic study with a cross-sectional approach. The level of periodontal pocket depth was analyzed by probing. Twenty-seven subjects were divided into three groups, namely, group 1 (with normal pocket depth: 0-3.5 mm), group 2 (pocket depth of 3.6-5.5 mm), and group 3 (pocket depth of more than 5.5 mm). GCF sampling was conducted by the infraclavicular method using paper points and its weight measurement wit han analytical balance. Data were analyzed by one-way analysis of variance followed by post hoc Tukey test to determine the comparison of GCF's weight between groups. The correlation was determined using the Pearson correlation test. Results: The average of GCF's weight obtained respectively in each group was 0.352 ± 0.09 mcg, 0.598 ± 0.10 mcg, and 0.899 ± 0.06 mcg. There was a significant difference (p < 0.001) with the highest GCF's weight was found in the pocket depth group >5.5 mm. The Pearson correlation test showed that there was a positive correlation between the depth of the periodontal pocket and the weight of GCF. Conclusion: The level of periodontal pocket depth is related to the weight of GCF.